2023
DOI: 10.36941/mjss-2023-0003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Drug and Substance Abuse among Secondary School Students in Zimbabwe

Abstract: The study was premised on factors that influence secondary school students’ participation in drug and substance abuse activities. In this context for data generation, analysis, and discussion, was guided by a framework comprised of the phenomenology and qualitative approach. For this study thirty students and six class teachers from one secondary school in Zimbabwe were purposively and conveniently sampled as sources of information for the issue under investigation respectively. Document analysis, focus group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The findings from the field survey conducted among secondary school students in North-Eastern Nigeria in 2023, which highlight the importance of measures such as sensitization campaigns, parental guidance, and law enforcement in addressing drug abuse, are supported by previous studies. Reference Pinias & Enia (2023) surveyed factors influencing drug and substance abuse among secondary school students in Zimbabwe and found that sensitization campaigns and parental guidance effectively prevented drug abuse. Reference Liu et al (2022) explored the relationship between parenting styles and adolescent drug abuse and emphasized the role of parental guidance and monitoring in preventing substance abuse.…”
Section: Preventive Strategies To Addressing the Menace Of Drug And S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the field survey conducted among secondary school students in North-Eastern Nigeria in 2023, which highlight the importance of measures such as sensitization campaigns, parental guidance, and law enforcement in addressing drug abuse, are supported by previous studies. Reference Pinias & Enia (2023) surveyed factors influencing drug and substance abuse among secondary school students in Zimbabwe and found that sensitization campaigns and parental guidance effectively prevented drug abuse. Reference Liu et al (2022) explored the relationship between parenting styles and adolescent drug abuse and emphasized the role of parental guidance and monitoring in preventing substance abuse.…”
Section: Preventive Strategies To Addressing the Menace Of Drug And S...mentioning
confidence: 99%
“…These studies provide further evidence of the adverse psychological effects of drug abuse and highlight the importance of addressing these issues to promote students' findings from the field survey conducted among secondary school students in North-Eastern Nigeria in 2023, which highlight the detrimental effects of drug abuse on academic performance, are supported by previous studies. ReferencePinias & Enia (2023) surveyed factors influencing drug and substance abuse among secondary school students in Zimbabwe and found that drug abuse negatively impacted academic performance. ReferenceTwekambe et al (2023) explored the psychosocial factors affecting antiretroviral therapy adherence among HIV-infected young adults in Eastern Uganda.…”
mentioning
confidence: 99%